The Association of Nutrition Status Towards The Outcome of Acute Ischemic Stroke Patients with Type-2 Diabetes Mellitus - Chaniago, Siti Alimahtun Sodiah; Nasution, Iskandar; Nasution, Irina Kemala (Journal of Society Medicine, 2023)
Introduction: Stroke is a sudden-onset neurologic deficit and having a type 2 diabetes increases the risk of stroke twice as much. In addition to affecting physical and mental abilities, stroke can also lead to a decline in nutritional status. Malnutrition is associated with poor functional outcomes in all stroke subtypes. The Controlling Nutritional Status (CONUT) score is an objective nutritional marker and could reflects malnutrition due to its comprehensive assessment of nutritional status. This study aims to find the association between nutritional status towards the outcome of acute ischemic stroke patients with type 2 diabetes. Method: This was an observational analytic study with prospective cohort design using primary data collected consecutively from patients with both acute ischemic stroke and type 2 diabetes mellitus who were hospitalized in the Stroke Corner Room, Intensive Care Unit (ICU) and inpatient ward of Haji Adam Malik General Hospital who met the inclusion criteria. The nutritional statuses of patients were measured using the CONUT score and patients outcomes were measured by mRS score. Spearman correlation test was used to assess the association between nutritional status and outcome of acute ischemic stroke patients with type 2 diabetes mellitus. Results: There were 43 patients who met the inclusion criteria where the majority of patients were male 22 people (51.2%), in the age group 51-65 years 23 people (53.5%) with a mean age of 57.93 + 10.01, was a housewife 15 people (34.9%) and Bataknese 27 people (62.8%). The majority of patients in this study had mild malnutrition with a total of 15 people (34.9%) and a median CONUT score of 3 (0-11) and poor outcome as many as 29 people (67.4%) with mRS score median 4 (0-6). The result of  Spearman correlation test showed a significant correlation between nutritional status and the outcome of acute ischemic stroke patients with type 2 diabetes mellitus with a moderate correlation. Conclusion: There was a significant correlation between nutritional status and the outcome of acute ischemic stroke patients with type 2 diabetes mellitus with a moderate correlation